Photocatalytic Hydrogen Evolution from Silica-Templated Polymeric Graphitic Carbon Nitride-Is the Surface Area Important? - Li, Xiaobo; Masters, Anthony F.; Maschmeyer, Thomas (ChemCatChem, 2015)
Low‐surface‐area, mesoporous silica‐templated polymeric graphitic carbon nitride (SBA–g‐C3N4), when irradiated with visible light, exhibits a greatly improved photocatalytic hydrogen evolution rate as compared to that of conventional bulk g‐C3N4 synthesized directly from the condensation of dicyandiamide. It also performs very similarly to high‐surface‐area mesoporous g‐C3N4 on a per‐unit mass basis. However, on the per‐unit area basis it greatly outperforms the other materials. The intrinsically high surface activity of SBA–g‐C3N4 was confirmed by using two different co‐catalysts, in situ photodeposited Pt and a structurally well‐defined molecular cobaloxime. Instead of the magnitude of the surface area as the dominant feature that determines activity, it was established that the high activity of SBA–g‐C3N4 results from a much higher number of delocalized electrons present and a suppressed recombination probability of photogenerated electron–hole pairs. More H2 through silica templating: Mesoporous‐silica‐templated, low‐surface‐area, polymeric graphitic carbon nitride (SBA–g‐C3N4) exhibits a greatly improved photocatalytic hydrogen evolution rate on a per‐surface area basis compared to that of conventional bulk graphitic carbon nitrides. The intrinsically high surface activity of SBA–g‐C3N4 was confirmed for both homo‐ (cobaloxime) and heterogeneous (Pt) co‐catalyst systems (TEOA=triethanolamine).